Peran QA dalam Meningkatkan Pengalaman Pengguna Aplikasi Dompet Duafa: Fokus pada Performa dan Fungsionalitas - Eko; Fadilah, Muhamad Ilham; Syukron, Muhammad; Saputra, Oki; Saifudin, Aries (Journal of Research and Publication Innovation, 2024)
This research explores the role of Quality Assurance (QA) in enhancing the user experience of the Dompet Duafa application, with a specific focus on performance and functionality aspects. Dompet Duafa, as a technology-based financial application, plays a crucial role in facilitating users in managing their finances. QA is key to ensuring that this application not only functions well but also provides an optimal user experience. The research emphasizes the importance of employing thorough testing methods for performance and functionality to address potential software quality issues. It identifies software quality problems that may arise and describes the consequences that may occur if these issues are not addressed properly. The findings of this research provide insights into how the effective implementation of QA, through meticulous testing methods, can enhance the performance and functionality of Dompet Duafa, thereby delivering a more satisfying user experience.